2012
DOI: 10.1002/aenm.201100783
|View full text |Cite
|
Sign up to set email alerts
|

Electrodeposited MnOx Films from Ionic Liquid for Electrocatalytic Water Oxidation

Abstract: A novel method for the electrodeposition of highly active water oxidation catalysts is described. The manganese oxide (MnOx) films are electrodeposited on fluorine tin oxide (FTO) glass substrate at high temperature (120 °C) from an ionic liquid electrolyte (ethylammonium nitrate). A range of analytical techniques, including X‐ray absorption spectroscopy (XAS), X‐ray diffraction (XRD), and energy‐dispersive X‐ray analyzer (EDX), indicate that the valence state of manganese in the deposited films can be control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
130
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(134 citation statements)
references
References 66 publications
4
130
0
Order By: Relevance
“…Based on this, we can assume that at both pH 7a nd 13 Mn 2 O 3 shows as uperior OER activity compared to MnO(OH). This agreesw ell with recent findings by Zhou et al [25] and Ramirez et al [74] who reported that Mn 2 O 3 species are the most active electrocatalytic Mn-containing compounds with respectt ot he OER. Based on the cationic distribution (Table S1), the surfaceo fs ample 2( 0.37 %) containsl ess Mn than that of sample 1( 0.84 %).…”
Section: Catalytically Active Speciessupporting
confidence: 90%
See 1 more Smart Citation
“…Based on this, we can assume that at both pH 7a nd 13 Mn 2 O 3 shows as uperior OER activity compared to MnO(OH). This agreesw ell with recent findings by Zhou et al [25] and Ramirez et al [74] who reported that Mn 2 O 3 species are the most active electrocatalytic Mn-containing compounds with respectt ot he OER. Based on the cationic distribution (Table S1), the surfaceo fs ample 2( 0.37 %) containsl ess Mn than that of sample 1( 0.84 %).…”
Section: Catalytically Active Speciessupporting
confidence: 90%
“…MnO x compounds with different compositions, morphologies, and structures have been synthesized using avariety of approaches and studied as water-splitting catalysts, for example, at pH 13 and 14. [24,25] Different Ni-,C o-,o rN i-Co-containingo xidess uch as LaMnO 3 , [26] LaNiO 3 , [27] graphene-Co 3 O 4 nanocomposites, [28] and NiCo 2 O 4 [22,29] have been investigated intensively over the The surfaceo fs teel S235 was oxidizedb yC l 2 gas and checked for its electrocatalytic efficiencyr egarding oxygen formation in aqueous solution.I fe xposed to humid Cl 2 gas for 110min, steel S235 became an electrocatalyst that exhibits an overpotential for the oxygen evolution reaction (OER) of 462 mV at 1mAcm À2 at pH 7. The OER activity of the same sample at pH 13 was moderate (347 mV overpotential at 2.0 mA cm À2 current density) in comparison with OER electrocatalysts developed recently.P otential versus time plots measured at ac onstant current demonstrate the sufficient stability of all samples under catalysis conditions at pH 7a nd 13 for tens of hours.…”
Section: Introductionmentioning
confidence: 99%
“…The same team also investigated the electrodeposition of Mn-oxides for the OER from ionic liquid electrolytes at elevated temperatures. 66 Electrodepositions were conducted galvanostatically at 120 °C from an electrolyte consisting of 10 mM manganese(II) acetate in a 1:9 mixture of water and ethylammonium nitrate. Various film morphologies were obtained as a function of the acidity of the electrolyte, including nanowires, nanofibres and nanoparticles.…”
Section: Electrodeposited Catalysts For Water Oxidation Based On Mangmentioning
confidence: 99%
“…[60] Recently, Spiccia et al modeled water-oxidizing manganese(III/IV) oxide and prepared a screen-printed material containing nanostructured manganese by means of redox precipitation that was highly active towards electrochemical water oxidation whereas manganese oxide films electrodeposited from ionic liquids were also investigated for the same purpose. [61][62][63] In the meantime, Jaramillo et al described excellent electrocatalytic activities of nanostructured manganese oxides towards oxygen evolution that could even act as a bifunctional catalyst for water oxidation with activities comparable to other highly active materials. [64][65][66] An attempt to correlate the structures of different crystalline polymorphs of manganese oxides with the catalytic activities for water oxidation was made by Dismukes et al [67] Thorough investigation of the bonding sites indicated that the asymmetrically occupied antibonding electron e g led to Jahn-Teller distortion in the system, which induced flexibility in the structure that promotes effective water oxidation.…”
Section: Introductionmentioning
confidence: 98%